2012
DOI: 10.1007/s10753-012-9566-y
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Inhibits DMBA/TPA-Induced Skin Tumorigenesis in Mice by Modulating Proliferation, Apoptosis, and Inflammation

Abstract: Baicalein, one of the four major flavanoids extracted from the root of Scutellaria baicalensis, has been shown to exert chemopreventive effect against several cancers, including skin cancer. However, the precise mechanisms remain to be elucidated. In the present study, we investigated the chemopreventive activity of baicalein against 7,12-dimethylbenz[a]anthracene (DMBA)/12-O-tetradecanoylphorbol-13-acetate (TPA)-mediated skin tumorigenesis in C57BL/6 mice. We found that topical treatment with baicalein result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…In fact, baicalein treatment inhibited cell proliferation and induced apoptosis. Furthermore, baicalein suppressed inflammation in DMBA/TPA induced skin cancer and reduced skin hyperplasia, as well as leukocyte infiltration [58]. Ezrin is highly expressed in skin cancer, plays an important role in the metastasis of tumors, and was found to be involved in the inhibition of skin carcinoma by baicalein.…”
Section: Baicalein and Melanoma/skin Cancermentioning
confidence: 99%
“…In fact, baicalein treatment inhibited cell proliferation and induced apoptosis. Furthermore, baicalein suppressed inflammation in DMBA/TPA induced skin cancer and reduced skin hyperplasia, as well as leukocyte infiltration [58]. Ezrin is highly expressed in skin cancer, plays an important role in the metastasis of tumors, and was found to be involved in the inhibition of skin carcinoma by baicalein.…”
Section: Baicalein and Melanoma/skin Cancermentioning
confidence: 99%
“…Previous investigations showed that baicalein exerts chemopreventive effects against several types of cancer [39], and that its anti-inflammatory and cyto-protective activities are predicated on anti-oxidative and radical quenching properties [40][41][42][43]. Furthermore, baicalein has pro-apoptotic activities given its ability to induce Ca 2+ -dependent mitochondrial dysfunction and to influence reactive oxygen species (ROS)-mediated pathways [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown to inhibit the expression of TNF and IL-6, thus enhancing recovery from infection [43]. Scutellaria baicalensis was reported to be able to remove free radicals, have antioxidant and anti-inflammatory effects, inhibit replication of Staphylococcus aureus and Streptococcus hemolyticus , and inhibit the migration of inflammatory cells, thereby alleviating local inflammation [44, 45]. Propolis extract has been shown to inhibit growth of pathogenic microorganisms, inflammatory reactions, and ulcers and to alleviate pain [46].…”
Section: Discussionmentioning
confidence: 99%